The Internet explosion, digital media principles and implications to communicate effectively in the digital space. (January 2018) - Reyna, Jorge; Hanham, Jose; Meier, Peter
Being literate has traditionally meant being able to read and write using the media of the day. In the 21st century, being literate requires additional skills such as competence with digital media creation. Until recently, those who could afford and use equipment and applications to produce digital media content were typically developers and technicians. With the development of prosumer electronics, in conjunction with the use of mobile devices and tablets, a shift has occurred in the accessibility of these tools, becoming more affordable for the general population. Video sharing services, social software and Web 2.0 applications have made it possible to host a digital media ecosystem on the Internet, and this has led to the proliferation of User-Generated Content. These technological advances have changed how we communicate, socialise and learn. Effective communication using digital media is underpinned by a set of design principles which most students are not likely to be aware. This paper built on two previous papers on the Digital Media Literacy Framework and the Taxonomy of Digital Media types for teaching and learning. It argues the importance of digital media principles to develop effective communication in the digital space. Students now require knowledge of these principles, in conjunction with conceptual and functional skills, for effective communication in the digital space.